Kepanikan Moral dan Politics of Moral di Sumatera Barat - Yayuk Lestari (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
This paper examines the discourse surrounding morality and politics. Taking the setting in West Sumatra, this paper intends to explore how local politicians use the issue of moral politics by spreading fear without solid evidence. The purpose of this article is to look at the intersection between morality and politics from the perspective of the sociological framework of “moral panics”, where the authorities, especially the government and religious institutions, are still the holders of authority to control the moral standards of society. By using the basis of adat and religion, the government negates LGBT groups for political purposes to gain mass support.